Effects of humidity and temperature on the non-linear elasticity of rocks. Issue 3 (31st July 2022) - Feng, Xuan; Fehler, Michael; Burns, Daniel; Brown, Stephen; Szabo, Thomas L
SUMMARY: Small velocity changes, associated with the non-linear response of rocks within the Earth, have been measured from dense arrays of seismometers to observe crustal deformation, the influence of solar heating and in situ pore pressure changes. Characterization of the non-linear elastic response of rocks provides new insight into rock microstructure and possibly new ways to determine the presence and type of fluid in the pore space. We conducted a long-term experiment to understand the influence of humidity and temperature on the non-linear elastic properties (NEPs) of rocks. The relative velocity change (d v / v ), a NEP, is computed from the time of flight delay caused by the presence of a superposed high amplitude ultrasonic signal in a sandstone sample within a controlled environmental chamber. Our phenomenological model for diffusion of humidity into the pore space fits the d v / v data exceptionally well, showing the d v / v is a linear function of humidity. We subtract the d v / v predicted by the humidity diffusion model from the measured d v / v to get a residual d v / v . This residual d v / v can be well fit by a temperature diffusion model in which the d v / v is a linear function of temperature. We suggest that d v / v is a sensitive indicator of moisture in pore spaces of rock and the temperature of the rock.